2006
DOI: 10.1016/j.ijpsycho.2005.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary stimulus production enhances deviance processing in the brain

Abstract: Humans often get information by voluntary action. However, little is known about how stimulus processing is modulated by self-production of stimuli. In the present study, event-related brain potentials were recorded from sixteen student volunteers performing an auditory three-stimulus oddball task in two conditions. In the self condition, the stimuli were triggered by participants' voluntary button presses. In the auto condition, the same stimuli were presented automatically by a computer with the same interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 30 publications
6
28
4
Order By: Relevance
“…The reason for a longer-than-usual peak latency (about 550 ms) of the LPP may be because it took time to compare the second stimulus with the cue stimulus, as in a kind of memory search task (Verleger, 1997). Contrary to the previous experiments (e.g., Nittono, 2006), no frontocentral P3a appeared in the present study. This result is reasonable because the two types of visual stimuli after actions (i.e., left or right) were presented equiprobably and neither was novel nor distracting.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The reason for a longer-than-usual peak latency (about 550 ms) of the LPP may be because it took time to compare the second stimulus with the cue stimulus, as in a kind of memory search task (Verleger, 1997). Contrary to the previous experiments (e.g., Nittono, 2006), no frontocentral P3a appeared in the present study. This result is reasonable because the two types of visual stimuli after actions (i.e., left or right) were presented equiprobably and neither was novel nor distracting.…”
Section: Discussioncontrasting
confidence: 83%
“…Previous studies have shown that the frontocentral P3 (P3a) elicited by rare deviant stimuli is enhanced when a participant controls the initiation of stimulus presentation by pressing a single trigger button, compared to when a computer controls the stimulus initiation without a participant's action (Nittono, 2004;Nittono and Ullsperger, 2000). This result is interpreted as indicating that action or action planning activates perceptual representation of the most probable action effect and the deviance from the expectation is reflected as the P3a enhancement (Nittono, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…This pattern of results has been interpreted to mean that action planning activates a perceptual representation of the most likely outcome of the action and that a perceived deviation from this expected outcome enhances the P3 (Nittono 2006;Waszak and Herwig 2007).…”
Section: Introductionmentioning
confidence: 90%
“…In this way, expectancy can indirectly affect the internal representation of time (Brown, 1997;Grondin, 2010;Lejeune, 1998;Debener, Kranczioch & Engel, 2002;Horvath, Roeber, Bendixen & Schroger, 2008;Nittono, 2006;Coull, 1998;Tse, Intriligator, Rivest & Cavanagh, 2004). Therefore, a possible interpretation of the results presented in this work is that unexpected changes in feedback engage bottom-up attentional mechanisms that interact with timing mechanisms (Humphreys et al, 1999;Debener et al, 2002).…”
Section: Overview Of Experimental Findingsmentioning
confidence: 78%
“…This pattern was noted in all experiments, suggesting that expectancy mechanisms interact with timing in the same way irrespective of the magnitude or nature of the manipulations. Studies using event-related potentials (ERPs), which is an electrophysiological index of brain processes with high temporal resolution, suggest that unpredicted sensory outcomes of voluntary actions are processed as deviant events (Waszak & Herwig, 2007;Nittono & Ullsperger, 2000;Nittono, 2006;Heinks-Maldonado et al, 2005;Adachi, Morikawa & Nittono, 2011). Unpredictable stimuli may also be viewed as distractors, given that unexpected events comprise an involuntary attention shift from the task-relevant information (in this case, timing) to nontemporal information.…”
Section: Overview Of Experimental Findingsmentioning
confidence: 99%